Model and Method of Intellectualization of the Processes of Providing Resources and Services of the Multiservice Network - O.S. Rayimjonova; I.A. Makhmudov; M.G. Tillaboyev (Genius Journals, 2022)
In this article, many factors are important in the organization of multiservice networks such as transport technology, services, service management, access to information resources, etc. Issues such as aspects of the implementation of similar factors on a network scale and the improvement of the network using modern technologies are one of the current issues. The organization and application of multiservice networks requires the solution of a number of issues, that is, it entails the solution of such issues as improving the efficiency of operation of multiservice networks, managing processes in them, and ensuring the durability of the system
Keywords: multiservice; networks; NGN; MSN